Body Composition of Common Bottlenose Dolphins in Sarasota Bay, Florida - Stephanie K. Adamczak; Rachel R. Holser; Daniel P. Costa; Elizabeth J. Berens McCabe; Randall S. Wells (Frontiers in Marine Science, 2021)
Marine mammal body composition has been an important tool that is used as a proxy for the health and condition of individuals within a population. Common bottlenose dolphin ( Tursiops truncatus ) body composition is influenced by variations in blubber thickness resulting from changes in temperature, prey availability, health, and life-history traits. We examined how environmental, ontogenetic, and reproductive variables influenced the body composition of common bottlenose dolphins in Sarasota Bay using data collected from a long-term monitoring project by the Sarasota Dolphin Research Program (SDRP). We found that both sea surface temperature (SST) and catch per unit effort (CPUE), used as a proxy for prey availability, influenced body composition. There was a high degree of seasonality in body composition, with higher values occurring in winter when SST and CPUE were both low. Ontogeny also greatly influenced body composition, as younger dolphins typically had thicker blubber than mature individuals. Interestingly, young females allocated more energy to allometric growth than deposition of blubber for body composition when compared to young males. However, as females matured and their growth slowed, they invested more in body composition. We found no significant difference in body composition of females of varying reproductive states, providing further evidence of their status as true income breeders. Our work highlights that changes in body composition result from fluctuations in environmental variables and that energy allocation to body composition changes with ontogeny.